Self-sufficiency challenges of blood products in LMICs and role of diplomacy - Rizky, Isnaniyah; Sjaaf, Amal Chalik (BKM Public Health and Community Medicine, 2023)
Purpose: PDMPs are one of the therapeutic substances derived from human blood and have a role in treating several life-threatening diseases. PDMPs are also included in the WHO Essential Medicines list. PDMP production development has been successful in developed countries. In contrast to LMIC countries, blood management is far from the standard. This issue is undoubtedly a challenge for developing countries. Besides, health diplomacy is suitable for solving the gaps in some health system problems. Methods: This writing uses a systematic review to collect information related to the challenges experienced by developing countries in implementing plasma fractionation and strategies that are ably implemented to increase the supply of PDMP. Results: The main challenges in implementing domestic fractionation by LMICs are collecting raw materials that need to meet standards, finances to fulfill fractionation facilities, and the need for more local teams with expertise in plasma fractionation. This also highlights how health diplomacy utilization can fill the gaps. Conclusion: Technological transformation is the key to success at each stage of the implementation of contract fractionation towards domestic fractionation, which will strengthen the resilience of the pharmaceutical industry in each LMIC country. It is also necessary to consider the benefit of establishing health diplomacy.